2020
DOI: 10.1136/bmjdrc-2019-000937
|View full text |Cite
|
Sign up to set email alerts
|

Air pollution and gestational diabetes mellitus: evidence from cohort studies

Abstract: Exposure to different air pollutants has been linked to type 2 diabetes mellitus, but the evidence for the association between air pollutants and gestational diabetes mellitus (GDM) has not been systematically evaluated. We systematically retrieved relevant studies from PubMed, Embase, and the Web of Science, and performed stratified analyses and regression analyses. Thirteen studies were analyzed, comprising 1 547 154 individuals from nine retrospective studies, three prospective studies, and one case–control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 52 publications
0
17
0
Order By: Relevance
“…Recent meta-analyses on NO 2 and GDM report either null associations [19,22] or marginal (and imprecise) pooled effect estimates [18,20,21]. Prior evidence on associations between PM 2.5 and gestational diabetes during pregnancy is also inconsistent [17][18][19][20][21][22]. We also observed differing results for residential greenness depending on which metabolic outcome was under investigation, as well as on which metric was used.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…Recent meta-analyses on NO 2 and GDM report either null associations [19,22] or marginal (and imprecise) pooled effect estimates [18,20,21]. Prior evidence on associations between PM 2.5 and gestational diabetes during pregnancy is also inconsistent [17][18][19][20][21][22]. We also observed differing results for residential greenness depending on which metabolic outcome was under investigation, as well as on which metric was used.…”
Section: Discussionmentioning
confidence: 66%
“…In contrast, we found inverse associations for elevated total triglycerides. Recent meta-analyses on NO 2 and GDM report either null associations [19,22] or marginal (and imprecise) pooled effect estimates [18,20,21]. Prior evidence on associations between PM 2.5 and gestational diabetes during pregnancy is also inconsistent [17][18][19][20][21][22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The finding that second trimester is a sensitive window of exposure for higher pregnancy glucose levels aligns with findings from previous studies evaluating the association between PM 2.5 and GDM. In fact, a recent systematic review of cohort studies found that only second-trimester exposure affects glucose homeostasis [ 10 ]. As such, this present study may further support the possibility that the radiometric component of PM could not only impact GDM, but also, more subtly, pregnancy glucose levels that do not meet the clinical threshold for GDM.…”
Section: Discussionmentioning
confidence: 99%
“…Several air pollutants, specifically nitrogen dioxide, nitrogen oxides, sulfur dioxide, and particulate matter (PM) with an aerodynamic diameter ≤ 2.5 μm (PM 2.5 ), have been previously identified to be associated with an increased risk of GDM [ 10 ]. While PM 2.5 during pre-pregnancy and the first trimester appear to have a null association with GDM, second-trimester exposure to PM 2.5 has been found to be associated with glucose metabolism [ 10 ]. Oxidative stress and inflammation from PM 2.5 are thought to be the primary mechanisms by which this exposure might increase GDM risk [ 11 ].…”
Section: Introductionmentioning
confidence: 99%